(untitled) (Journal of Economic Research & Business Administration, 2016)
Investment activity – it is investing, or an investment, and a set of practical steps for the implementation of investments. Investing in the creation and reproduction of fixed assets carried out in the form of capital investment. In order to determine the optimal direction of capital investments and to identify the most effective ways to use it for quite a long period of stable returns, it is necessary to develop a successful investment strategy and its implementation. More detailed investment priorities for the chosen strategy are determined by analyzing the features of the company, its position in the market, the level of specialization, the structure of the production portfolio. At the last position all enterprises and their associations can be divided into one activity involved (specialized) and several types of activities (diversified). This article described in detail the value of the investment policy of innovative enterprises, as well as their structure and reproduction steps investments. At the same time, it is said about the importance of the investment policy, to the company’s business strategy.